Lost lives, new voices : unlocking the stories of the Scottish soldiers from the battle of Dunbar 1650 - Gerrard, Christopher M.; Graves, Pam; Millard, Andrew; Annis, Richard; Caffell, Anwen (Oxbow Books, 2018)
In November 2013 two mass burials were discovered unexpectedly on a construction site in the city of Durham in north-east England. Today we know them to be some of the Scottish prisoners who died in the autumn of 1650 in Durham cathedral and castle following the battle of Dunbar on the south-east coast of Scotland. Fought between the English and the Scots, this was one of the key engagements of the War of the Three Kingdoms. Using the latest techniques of skeleton science, this book gives back to the men a voice through an understanding of their childhood and later lives. Archaeological and historical evidence also allows us to reconstruct with vivid accuracy how and why these men vanished off the historical radar. Of the prisoners who survived their ordeal after Dunbar, new evidence has emerged about their involvement in local industries and in one of the great infrastructural projects of the day, the draining of the Fens. Others were sent far away, transported to the colonies as indentured servants to begin a new life at the edge of the known world. Following the trail of their biographies takes us across the Atlantic where the Dunbar men supported each other throughout their lives on the frontiers of New England.